The Influence of Financial Literature on The Spirit Of Entrepreneurship on Students of Islamic Primary School - Dewi, Tri Ratna; Rohmah, Miftakhur (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The objectives of this study are 1) Knowing how to implement Financial Literacy education for children in MI East OKU. 2) Knowing how the entrepreneur spirit in children in MI East OKU. 3) Knowing how big the influence of financial literacy on the entrepreneur spirit of the children of MI East OKU. The method used is mixed methods. Qualitative methods are used to find the hypothesis, while quantitative methods are used to test research hypotheses. Sampling using purposive sampling technique by determining the criteria for financial literacy and entrepreneur spirit. The sample in this study was MI Nurul Iman with MIN 02 East OKU based on observations that met the criteria. Qualitative data collection techniques using observation and interviews while quantitative using a questionnaire. Quantitative data analysis techniques using calculations and simple linear regression.  Based on calculations, financial literacy data obtained a value of 73% of the expected. While the entrepreneur spirit of students is 75% of what is cultivated. Furthermore, the effect of the two using simple linear regression obtained sig of 0.029 <0.05 so it can be concluded that H0 which reads there is no influence between financial literacy on the entrepreneur spirit of students is rejected, and Ha is accepted which means that there is an influence between financial literacy on the entrepreneur spirit of students. From the results of the study, it can be concluded that there is an influence of the application of financial literacy on the entrepreneur spirit of children in MI East OKU.